2020
DOI: 10.1002/fsn3.1918
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Habits and their Association with Metabolic Syndrome in a sample of Iranian adults: A population‐based study

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 67 publications
0
16
0
Order By: Relevance
“…Increasing in carbohydrate consumption is associated with the risks of CVD or other components of Mets by high intakes of energy and glycemic load (4,7) . However, most of these outcomes are controversial, for instance in a study, sugar and sweetened beverage consumption did not have any significant effect on Mets (8) . Therefore, investigating the effect of macronutrients intake within a dietary pattern can help evaluate the association between diet and diseases (9,10) .…”
mentioning
confidence: 98%
“…Increasing in carbohydrate consumption is associated with the risks of CVD or other components of Mets by high intakes of energy and glycemic load (4,7) . However, most of these outcomes are controversial, for instance in a study, sugar and sweetened beverage consumption did not have any significant effect on Mets (8) . Therefore, investigating the effect of macronutrients intake within a dietary pattern can help evaluate the association between diet and diseases (9,10) .…”
mentioning
confidence: 98%
“…Takebe et al reported that, in participants aged older than 20 years, skipping breakfast was correlated with weight gain (OR 1.252, compared with a regular breakfast) [ 14 ]. A cross-sectional study in Iran showed that, among adult participants, breakfast consumption habits had a significant negative impact on the occurrence of metabolic syndrome (OR = 0.38) [ 13 ]. A South Korean study reported that consuming breakfast less frequently increases the risk of dyslipidemia [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that skipping breakfast is related to adolescent cardiometabolic risk factors such as an altered lipid profile [ 17 ]. Previous studies have found that metabolic syndrome is inversely related to breakfast consumption frequency [ 13 , 18 ]. Weight gain is also associated with the consumption of breakfast [ 14 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, some studies have clearly shown that lifestyle interventions, such as nutritional management and the promotion of exercise, reduces the risk of MetS [ 17 , 18 , 19 , 20 ]. In addition, eating habits, such as eating speed and skipping breakfast, walking speed and sleep, have also been reported to be associated with MetS [ 21 , 22 , 23 , 24 ]. Thus, in addition to diets and physical inactivity, various other lifestyle factors are relevant and warrant attention.…”
Section: Introductionmentioning
confidence: 99%